2016
DOI: 10.1002/jnr.23840
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic regulation of fear learning and extinction

Abstract: Cholinergic activation regulates cognitive function, and particularly long term memory consolidation. Here we present an overview of the anatomical, neurochemical, and pharmacological evidence supporting the cholinergic regulation of Pavlovian contextual and cue conditioned fear learning and extinction. Basal forebrain cholinergic neurons provide inputs to neocortical regions and subcortical limbic structures such as the hippocampus and amygdala. Pharmacological manipulations of muscarinic and nicotinic recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 129 publications
(230 reference statements)
2
59
0
1
Order By: Relevance
“…These attentional effects might be mediated via orexin effects in the basal forebrain cholinergic system, or direct modulation of attentional processes in regions like the prefrontal cortex [25]. OxB activates basal forebrain cholinergic neurons [88], and cholinergic regulation influences both consolidation of fear memories and extinction [89]. OxA injections into the basal forebrain or the PFC enhance acetylcholine release in the PFC, and either intrabasalis or i.c.v.…”
Section: 0 Discussionmentioning
confidence: 99%
“…These attentional effects might be mediated via orexin effects in the basal forebrain cholinergic system, or direct modulation of attentional processes in regions like the prefrontal cortex [25]. OxB activates basal forebrain cholinergic neurons [88], and cholinergic regulation influences both consolidation of fear memories and extinction [89]. OxA injections into the basal forebrain or the PFC enhance acetylcholine release in the PFC, and either intrabasalis or i.c.v.…”
Section: 0 Discussionmentioning
confidence: 99%
“…The NTS has direct and indirect projections to brain regions that mediate learning and memory. In addition to VNS effects on norepinephrine release from the LC, activity in the basal forebrain is increased following VNS and there is evidence that acetylcholine signaling in the amygdala, hippocampus, and prefrontal cortex acts to modulate memory for fear and extinction (Wilson and Fadel 2017). Stimulation of the vagus nerve also activates the dorsal raphe nucleus (DRN) via indirect projections from the LC and monosynaptic projections from the NTS.…”
Section: Introductionmentioning
confidence: 99%
“…While it is clear that mAChRs modulate the learning and memory functions of the hippocampus (Deiana et al, ; Thiele, ; Wilson & Fadel, ), the contributions of specific mAChR subtypes in mediating these effects remain unclear. Early immunohistochemical (Hersch & Levey, ; Levey et al, ) and in situ hybridization (Brann, Buckley, & Bonner, ; Buckley et al, ) studies showed predominant M1, M2, and M4 mAChR protein and gene expression within the hippocampus, with G i/o ‐coupled M2 and M4 receptors largely located presynaptically (Levey et al, ; Rouse, Edmunds, Yi, Gilmor, & Levey, ), and G q/11 ‐coupled M1 receptors largely located postsynaptically (Levey et al, ; Rouse et al, ; Volpicelli & Levey, ).…”
Section: Introductionmentioning
confidence: 99%